Micromachined passive phase-change cooler for thermal management of chip-level electronics. (October 2015) - So, Hongyun; Pisano, Albert P.
Highlights: Reliable passive cooling device was developed for chip-level electronics cooling. Microstructures and hierarchical wick allowed continuous feeding of coolant. Chronic dryout limitation was addressed by enhanced and extended capillary forces. Kinetic theory was introduced as a design tool to determine allowable heat flux. Chip heat flux of 32 W/cm 2 was successfully cooled down by the developed cooler. Abstract: This paper reports an efficient and reliable passive cooling device using phase-change of coolant in response to the needs of chip-level electronics applications in which heat dissipation must be removed as rapidly and continuously as possible. The design of this cooling device was developed with three functional layers including evaporator, wick, and reservoir, which provided enhanced capillary forces, allowing reliable cooling performance without wick dryout and coolant back flows. Cooling performance by the developed system was demonstrated experimentally with a combination of microfabrication techniques and nanomaterial synthesis, showing rapid and efficient heat removal ability by enhanced and extended capillary action during the operation. The chronic dryout limitation in micro cooling devices could be addressed by the proposed thermal system.